EFFECTS OF PRENATAL DEXAMETHASONE ON TERM INFANTS IN CASES OF MATERNAL ANTEPARTUM HEMORRHAGE: A CROSS-SECTIONAL STUDY (Student's Journal of Health Research Africa, 2025)
BackgroundIn the past 25 years, the use of prenatal corticosteroids in pregnant women who are about to give birth, typically between 24 and 34 weeks of gestation, has been one of the most important advancements in perinatal medicine. ObjectivesIn this investigation, the effects of maternal antepartum hemorrhage (APH) on the results of term children who were exposed to dexamethasone during pregnancy and those who were not. Materials and MethodsThe study was a retrospective study that was carried out at Hi-Tech Medical College, Bhubaneswar, Odisha, India. Information about 800 patients was extracted. Records pertaining to female patients suffering from APH who gave birth to a single child at 37 weeks or more. Exclusion criteria included those with premature rupture of the membranes or those who did not receive a full course of dexamethasone. ResultsThe study included 800 pregnant women, 40 receiving antenatal dexamethasone and 760 not. The dexamethasone group had a lower mean maternal age (31.5±4.3 vs. 34.2±4.2 years; p